INTEGRATION OF SUSTAINABLE DEVELOPMENT PRINCIPLES INTO THE ACTIVITIES OF UKRAINIAN UNIVERSITIES AS A TOOL FOR ENSURING THE QUALITY OF HIGHER EDUCATION - Олена Кузьмак (Економіка та суспільство)
The article analyzes the role of the implementation of the Sustainable Development Goals (SDGs) in ensuring the quality of education in universities in Ukraine. The main ways of integrating the principles of sustainable development into the educational process are outlined. Special attention is paid to the need to develop sustainable development strategies in universities, monitor and evaluate the implementation of the SDGs, and cooperate with state bodies, businesses, and public organizations. The importance of forming sustainable development values among university students and teachers and training specialists capable of solving sustainable development problems at the local and global levels is emphasized. The importance of integrating the SDGs for improving the quality of education in the context of European integration and global changes towards sustainable development is highlighted. Directions for improving the integration of the Sustainable Development Goals into Ukraine's universities' activities are proposed.